Assessment of cerebral perfusional and functional connectivity in schizophrenia using magnetic resonance imaging - Oliveira, Icaro Agenor Ferreira de; Guimarães, Tiago M; Souza, Roberto M; dos Santos, Antonio C; Sousa, Joao Paulo M; Hallak, Jaime E. C.; Leoni, Renata F (Revista Brasileira de Física Médica, 2017)
Schizophrenia is a significant mental disorder that compromises structural and functional aspects of the brain, with an extreme effect on the patient’s thoughts, feelings, and behavior. Physiologically, in addition to functional and structural abnormalities, changes in neuronal activity are reported. Since the cerebral blood flow (CBF) is directly related to neuronal activity, the magnetic resonance imaging (MRI) technique called arterial spin labeling (ASL), which allows the quantification of CBF, is a useful tool in brain perfusional evaluation. In addition, ASL can be used to assess functional connectivity, which is efficient in investigating functional impairment between regions of the brain. Pseudo-continuous arterial spin labeling (pCASL) images were acquired from 28 schizophrenia patients in treatment and 28 age-matched healthy controls. Static CBF and connectivity patterns were assessed. Decreased CBF and functional connectivity were observed in regions that forms two resting brain networks, default mode (DMN) and salience (SN), for schizophrenia patients. Previous studies related the features of this pathology with altered resting CBF and functional disconnections. Therefore, using a noninvasive technique, we were able to find CBF deficits and altered functional organization of the brain in schizophrenia patients that are associated with the symptoms and characteristics of the disorder.